STUDY ON CHARACTERISTIC OF REVERSE OSMOSIS (R O) SYSTEM IN CHIDAMBARAM TALUK, CUDDALORE DISTICT - Dr. S. Sivaprakasam, Dr. N. Nagarajan, Dr. K. Karthikeyan (International Journal of Advanced Science and Technology, 2020)
Water is the most important natural resources and is the basic need for all life on earth. The well-being and the development of our society are dependent on the water availability. People, interested in installing a water treatment system to reduce toxic substances, first should test the water which they are going to use and assess the presence and the quantum of hazardous ingredients in that water. In Chidambaram, ground water and municipal water is not pure and present with salt. So, reverse osmosis systems have been installed in many houses for obtaining potable water. The reverse osmosis system is a cost effective way for getting high eminence demineralized water with low water-rejection rate. It is a process in which the molecules would suddenly migrate through certain membranes that separate a dilute from a concentrated solution. If pressure is added to the higher contaminant solution, the natural flow can be reversed. This reversal allows the contaminant solution to be concentrated further and allows the purified water to be produced and the unit is called reverse osmosis water purification units. A reverse osmosis device consists of the membranes housing “pre” and “post” filters. This study involves the performance of household RO system installed in the residences in and around Chidambaram in removing the high TDS content present in source water obtained from shallow bore wells installed in the housing premises. But, the treated water gets demineralized and it causes some mineral deficiency disease to human. Therefore, it is advised to use treated water mixed with raw water.